Mediating Marginality Through Photography: Kent Klich's El niño: Children of the Streets, Mexico City. (2nd September 2018) - Gardner, Nathanial
Abstract: This article considers the book El niño: Children of the Streets, Mexico City, a text and image project by Swedish photographer Kent Klich and Elena Poniatowska published in New York in 1999 after a failed attempt to publish it in the Mexican capital. A comparative approach is taken as the themes of El niño 's photographic narrative are considered in the light of an earlier foreign project that confronted marginality in Mexico: Oscar Lewis's The Children of Sánchez . The role of the photographs and possible interpretations of them are explored. Analysis of the photographic contacts permits discussion on the development of visual representation and reveals Klich's nuancing in his portrayal of the street children.